PENERAPAN METODE TARTIL DALAM MENINGKATKAN KEMAMPUAN BACAAN AL-QUR'AN DI TAMAN PENDIDIKAN AL-MAUIZZAH KOTA BIMA (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
This study aims to analyze the implementation of the tartil method in improving Qur’an reading skills at Taman Pendidikan Al-Qur’an (TPA) Al-Muizzah, Bima City. The tartil method, which emphasizes slow and clear recitation of the Qur’an in accordance with tajwid rules, is applied to enhance the quality of students’ recitations. This research employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The findings indicate that the systematic and continuous application of the tartil method has successfully improved students’ Qur’an reading skills in terms of fluency, accuracy in applying tajwid, and articulation. In addition, this method also contributes to shaping students’ character, such as discipline and perseverance. However, the challenges faced include limited time during learning sessions and the varying ability levels of students. Nevertheless, this study concludes that the tartil method can serve as an effective alternative in improving the quality of Qur’an learning, by considering both technical and non-technical aspects in the learning process.